Forest Fire and Plant Invasion : Exploring the Agents of Land Degradation in a Tropical Deciduous Forest Landscape - Das, Suparna; Singh, Shubham; Das, Agnish Kumar; Bala, Nirmalya; Adhikari, Bhupendra Singh (Indian Forester, 2023)
Land degradation is one of the major environmental concerns of the 21st century. Forest fires and the spread of invasive aiien piant species have been considered as major drivers of forest degradation which have led to changes in the structure and composition of the forest, and also have led to a decline in the productivity of the forest The study explores a possible association of forest fires and the prevalence of invasive species in a tropical forest landscape. The present study has been conducted in the fire-affected areas of tropical moist deciduous forest dominated by Shorea robusta and also evaluates the effect of forest fire severity on invasion by invasive plants in and around Doon valley, Uttarakhand. The fire severity was mapped using the differenced Normalized Bum Ratio, and was used as a proxy for understanding the Impact of fire. Ecological data analysis was done through field study and Importance Value Index (IVI), and diversity indices were calculated. The results revealed the shrub diversity was higher in moderate fire severity regions. The occurrence of fire was observed to affect the presence of invasive species In a one-way ANOVA using total IVI of invasive species as the single factor per site. A clear association between total IVI of invasive species was observed and the presence of fire regardless of its severity, but a clear association between total IVI of invasive species and the severity of fire was not observed. The study infers that while the effect of the severity of fire is not clear on the presence of invasive species, but the presence of fire helps in the establishment o f invasive species. The study recommends long-term monitoring to understand if there is existing positive feedback between these two nefarious agents of forest degradation. The study would help future forest managers in developing management plans for sustainable management and restoration of the forests to its prime state.